2021
DOI: 10.1371/journal.pone.0260498
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme polymorphisms AND Alzheimer’s disease susceptibility: An updated meta-analysis

Abstract: Background Many studies among different ethnic populations suggested that angiotensin converting enzyme (ACE) gene polymorphisms were associated with susceptibility to Alzheimer’s disease (AD). However, the results remained inconclusive. In the present meta-analysis, we aimed to clarify the effect of ACE polymorphisms on AD risk using all available relevant data. Methods Systemic literature searches were performed using PubMed, Embase, Alzgene and China National Knowledge Infrastructure (CNKI). Relevant data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
0
10
1
Order By: Relevance
“…These findings are in line with preclinical studies [78][79][80] and emphasize the important role and multifactorial contribution of this gene cluster to ACD pathogenesis. Although previous literature points to an association of ACE with AD 81 but not VaD 82,83 , we herein show that this gene underlies both ACD and vascular risk factors. A recent study supports this finding by showing that overexpression of ACE on macrophages lead to reduction in vascular amyloid and GFAP+ astroglial reactivation, which indicate its role in protection of the neurovascular unit 84 .…”
Section: Discussioncontrasting
confidence: 71%
“…These findings are in line with preclinical studies [78][79][80] and emphasize the important role and multifactorial contribution of this gene cluster to ACD pathogenesis. Although previous literature points to an association of ACE with AD 81 but not VaD 82,83 , we herein show that this gene underlies both ACD and vascular risk factors. A recent study supports this finding by showing that overexpression of ACE on macrophages lead to reduction in vascular amyloid and GFAP+ astroglial reactivation, which indicate its role in protection of the neurovascular unit 84 .…”
Section: Discussioncontrasting
confidence: 71%
“…ACE and its expression have been implicated in genetic studies of AD. 31,32 In the largest GWAS study, the ACE SNP rs4277405 (minor C allele) was associated with lower risk of AD (OR = 0.94) in genome-wide level of significance, and by extension the major allele (T allele) is associated with increased AD risk. 7 The rs4277405 (T allele) was in LD with the ACE inhibition rs4343 SNP (A allele) that showed the strongest effect in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…204 Another recent study comparing AD patients to age and gender matched cognitively healthy controls demonstrated that the rs4646994 ACE gene polymorphism was also associated with increased AD risk. 205 Gene polymorphisms within the methylenetetrahydrofolate reductase (MTHFR) gene, which encodes a protein necessary for homocysteine metabolism, have been found to increase circulating Hcy levels and promote memory impairment and cognitive dysfunction, decrease cortical and hippocampal volumes, increase cerebral atrophy, and increase hippocampal apoptosis in mice. 206,207 In humans, the MTHFR gene polymorphism C677T (rs1801133), as well as MTHFR A1298C, were associated with increased late-onset AD risk.…”
Section: Genetic Risk Biomarkersmentioning
confidence: 99%
“…Interestingly, a recent metanalysis including 82 cohorts from 65 individual studies revealed significant associations between the rs1799752 ACE polymorphism and increased AD risk 204 . Another recent study comparing AD patients to age and gender matched cognitively healthy controls demonstrated that the rs4646994 ACE gene polymorphism was also associated with increased AD risk 205 . Gene polymorphisms within the methylenetetrahydrofolate reductase (MTHFR) gene, which encodes a protein necessary for homocysteine metabolism, have been found to increase circulating Hcy levels and promote memory impairment and cognitive dysfunction, decrease cortical and hippocampal volumes, increase cerebral atrophy, and increase hippocampal apoptosis in mice 206,207 .…”
Section: Clinical Trialsmentioning
confidence: 99%